Teachers’ self-regulated learning instructional practices: Differences in perception among TVET students in Cambodia - Chamnan Sok; Sarom Mok; Somony Som; Mengheang Hor; Sereyrath Em (Journal of General Education and Humanities, 2026)
A rising number of Cambodian students at all levels are attempting to improve their English language proficiency as a result of the growing demand for English language instruction. Self-Regulated Learning (SRL) techniques are crucial for student progress, yet their effective teaching in classrooms is frequently absent. This study used a unique methodology that concentrated on TVET students’ perception of their teachers’ encouragement of SRL techniques. In order to promote SRL during regular classroom instruction, ten TVET center teachers completed a professional learning program and sent in a video clip of their lessons. Thirty students participated in semi-structured stimulated recall interviews with these videos as stimuli. Students were instructed to use “What, When, Why, and How?” to explain how their teachers taught SRL strategies. It looked at relationships between teachers’ behaviors, methods of promotion, and choice of strategy type and situations in which students gave a clear explanation of the goal and potential for transfer of SRL strategies. The findings show that students were most aware of SRL instruction when it included the strategy’s name, a clear application procedure, teacher explanations of how and why the strategy enhances learning, and prompts to encourage students to give examples of transfer. These findings are presented in relation to how educators may effectively encourage SRL in the classroom.